Distal Cervical Carotid Artery Dissection after Carotid Endarterectomy: A Complication of Indwelling Shunt. (25th July 2010) - Tamaki, Tomonori; Yoji, Node; Saito, Norihiro
Abstract : The technical factors and surgical methods employed in carotid endarterectomy are controversial. In particular, whether or not to use an indwelling arterial shunt during carotid endarterectomy remains a source of conflict. We describe a rare case in which uncomplicated carotid endarterectomy was followed by distal internal carotid artery dissection and suggest that this devastating complication was due to intimal damage produced by the use of an indwelling arterial shunt.